STUDENTS' DESCRIPTIVE WRITING PERFORMANCES IN ONLINE ENGLISH LANGUAGE CLASSROOM - Farida Hamid; Siti Zulfa; Tungky Ariwibowo; Nida Husna; Didin Nuruddin Hidayat (IJEE (Indonesian Journal of English Education), 2022)
ABSTRACTDuring the Covid-19 situation, the online classroom activities assist teachers and students in achieving the learning objectives. The objectives of this study were to know students' performances and obstacles in the online descriptive writing English language classroom. The qualitative method was used as the research design. The data were collected through open-ended questionnaires, semi-interviews, and documents. The study involved one teacher and 30 students in senior high school through purposive sampling. The results indicated that students' performances were mostly good in the online descriptive writing learning activities following their high motivation and great attitude to participate in the online classroom. However, some problems persisted, such as a lack of vocabulary and confusion in generic structure text and grammatical use. In addition, the internet connection has become the main problem supporting students' performance during online classroom activities. Hence, adding more supporting and proper activities that can be applied online is needed. ABSTRAKSelama Covid-19, kegiatan kelas online membantu guru dan siswa untuk mencapai tujuan pembelajaran. Tujuan dari penelitian ini adalah untuk mengetahui kinerja siswa dan hambatan dalam menulis deskriptif online kelas bahasa Inggris. Metode penelitian yang digunakan adalah metode kualitatif. Pengumpulan data dilakukan melalui angket terbuka, semi wawancara, dan dokumen. Penelitian ini melibatkan satu orang guru dan 30 siswa SMA melalui purposive sampling. Hasil penelitian menunjukkan bahwa kinerja siswa sebagian besar baik dalam kegiatan pembelajaran menulis deskriptif online karena motivasi tinggi dan sikap mereka yang baik untuk berpartisipasi dalam kelas online. Namun, beberapa masalah masih tetap ada seperti kurangnya kosa kata dan kebingungan dalam memahami struktur teks umum dan penggunaan tata bahasa. Selain itu, koneksi internet menjadi kendala utama untuk menunjang kinerja siswa selama kegiatan kelas online. Oleh karena itu, sangat penting untuk menambah lebih banyak kegiatan yang mendukung dan tepat yang dapat diterapkan melalui online sangat diperlukan.